Dahschur, Ägypten. Die Arbeiten der Frühjahrskampagne 2019 - Rosenow, Daniela (e-Forschungsberichte des DAI, 2019)
The royal necropolis of Dahshur, with its unusually high amount of architectural remains from the construction time of the pyramids, offers a great potential for researching the administrative, logistic and technical requirements that made it possible to create some of the most impressive monuments ever created by humankind. A geomagnetic survey conducted in 2013 in the area north of the valley temple of the Bent Pyramid revealed the remains of a large settlement. First excavations here were undertaken in spring 2018 and continued this year. Our work aims at determining the nature of these buried structures: who lived here in the desert, when, and for what purpose? Furthermore archaeological work continued on a transportation road built during the Ramesside period (ca. 11th–13th century BC), while conservation and architectural research was undertaken on the cult place of the Bent Pyramid built by king Sneferu, the first pharaoh of the 4th dynasty (ca. 2650 BC).